2011
DOI: 10.1016/j.ejvs.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Ruptured Abdominal Aortic Aneurysm in Octogenarians

Abstract: Surgical mortality of ruptured aneurysm repair was not independently related to advanced age but mainly driven by cardiac disease and manifest hypovolaemic shock. An almost normal long-term prognosis of aged patients after successful repair justifies even attempts of open repair, particularly in carefully selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…1 Previously, several factors such as age, female sex, prolonged collapsed vital phase, massive transfusion, or hemorrhage during surgery, were considered independent risk factors of mortality. [2][3][4][5][6][7][8][9][10][11] However, these results are still not definitive and some studies were published in the 1990s. Between 2006 and 2012, 57 patients received emergency surgical treatment for AAA.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…1 Previously, several factors such as age, female sex, prolonged collapsed vital phase, massive transfusion, or hemorrhage during surgery, were considered independent risk factors of mortality. [2][3][4][5][6][7][8][9][10][11] However, these results are still not definitive and some studies were published in the 1990s. Between 2006 and 2012, 57 patients received emergency surgical treatment for AAA.…”
Section: Introductionmentioning
confidence: 83%
“…6,7,17 Although the elderly patients have an increased risk of having cardiac and cerebrovascular events in the postoperative period, 8 the risk factor might not be age itself but cardiac or some other capacities of these patients. 9 Regarding the blood data, previous studies reported hemoglobin or hematocrit levels indicated the degree of hemorrhage, and elevated serum creatinine level >1.5 mg/dL correlated with adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Swiss Cardiovascular Centre manages about a quarter of rAAAs in Switzerland17. In 2001, a cohort study was started to follow all patients with rAAA prospectively18. The study ran until December 2010.…”
Section: Methodsmentioning
confidence: 99%
“…The study ran until December 2010. Inclusion criteria and validation of consecutive completeness have been described previously18. In brief, all types of rAAA were captured including true, false and mycotic aneurysms at pararenal or infrarenal aortic and/or iliac level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation